Administrasi Kemitraan Sekolah MIS Al-Quba Dengan Stakeholder - Jeihan Fitrah Wardanah; Rindi Atika; Rania Muzdalifah (Pendekar : Jurnal Pendidikan Berkarakter, 2023)
His research aims to describe the implementation of school partnerships with stakeholders, knowing the benefits of these school partnerships. As well as knowing the supporting and inhibiting factors of MIS AL QUBA school. this research uses a qualitative description method. In addition, researchers also used a literature study research strategy. Data collection techniques used interviews, observations, and documentation studies. The subjects of this research involved the principal, teaching staff, student affairs, facilities and infrastructure, and students. The object of this research is MIS AL QUBA school. The results of the study show that the success of educational goals in a school institution besides depending on internal factors referred to as school residents, namely those consisting of principals, educators and education personnel, internal stakeholders are expected to carry out the teaching cycle and external stakeholders are needed as assistance to work on the nature of education, both of which are interrelated. And the inhibiting factor so far in the school's relationship with the local community. Stakeholders are the path to effective administration of an educational institution or school.